Evaluation of Toxicity Potential and Spatial Distribution of Ecological Risk of Heavy Metals in Surface Sediments of Anzali International Wetland Using GIS - Zhaleh Amini; Reza Anvaripour; masoud Hatami-manesh; Jaber Aazami (علوم محیطی)
Introduction; Due to the potential toxicity and ecological risk of heavy metals in aquatic ecosystems, measuring and evaluating their concentration in different parts of aquatic environments is very necessary. Therefore, the present study measures the concentrations of Cd, Cr, Pb, Ni, As and Zn and evaluates the spatial distribution of their ecological risk in the surface sediments of Anzali International Wetland.Materials and methods; 50 stations in different parts of the wetland were selected for sampling. After preparation and acid digestion of samples, the concentrations of these metals were determined by an atomic absorption spectrometer. In order to zoning the toxicity and ecological risk of metals, the inverse distance weighting (IDW) method was used.Results and discussion; The total mean concentrations of metals were Zn (79.24 71 6.71), Cr (19.4 21 21.04), Ni (18.96 62 5.62), Pb (13.3 72 72.50), As (7.62 96 4.96) and Cd (1.12 ± 3.16) mg/kg, respectively. Investigation of potential acute toxicity, RI, mHQ and PLI indicated low pollution status in wetland sediments. The environmental risk of the metals in the sediments were evaluated as (Cd> As> Pb> Ni> Zn> Cr). In addition, the distribution of toxicity and ecological risk of metals in different parts of the wetland does not follow the same pattern and the western parts of the wetland have more risks. Conclusion; According to the results, Potential acute toxicity, PLI, mHQ and ecological risk of heavy metals in the sediments of the region are assessed as low and medium. The intense expansion of human activities in the areas around the wetland, along with the deposition and entry of various pollutants in this ecosystem, confirms the need for continuous monitoring of the wetland and assessment of its ecological health risk.